Thermal Decomposition Kinetics of Ni(II) Chelates of Substituted Chalcones - K. G. Mallikarjun (E-Journal of Chemistry)
The thermal decomposition of Ni(II) complexes of 3-(phenyl)-1-(2’-hydroxy-naphthyl)-2-propen-1-one (PHPO), 3-(4-chlorophenyl)-1-(2’-hydroxy-naphthyl)-2-propen-1-one(CPHPO), 3-(4-methoxyphenyl)-1-(2’-hydroxynapthyl)-2-propen-1-one (MPHPO), 3-(3,4-dimethoxyphenyl)-1-(2’-hydroxynaphthyl)-2-propen-1-one(DMPHPO) was studied by thermogravimetry. Mathematical analysis of the data has allowed us to determine various parameters using Freeman-Carroll equation, the integral method using the coats-Redfern equation and the approximation method using the Horowitz-Metzger equation. The trend of the kinetic parameters was found to be different from that of the thermal stability order. The low values of Z suggest the slow nature of the reaction.